BIOLOGICAL CONTROL: ISOLATED AND IN MIXTURES AND GENETIC CONTROL OF Meloidogyne exigua IN COFFE - Tolardo, Alex Lavado; Alves, Gleina Costa Silva; da Silva, Gustavo Ferreira; Pereira, Wellington José; da Silva, Débora Zacarias; Silva, Samuel Afonso Sampaio (Coffee Science - ISSN 1984-3909, 2019)
Meloidogyne exigua is one of the most found species of nematodes in coffee plantations in the Brazilian Cerrado. Thus, the objective of the present study was to evaluate the efficiency of biological agents on two coffee cultivars. The experiment was carried out in a greenhouse using a completely randomized design. The treatments were arranged in a 2x3 factorial scheme, using repeated measures (two cultivars, 3 nematicides, and 2 additional controls), and were composed of two genotypes (Mundo Novo IAC 376-4 and IPR-100), three biological nematicides (B. methylotrophicus, B. subitilis, and T. asperellum), and two treatments including the three nematicides together, totaling 8 treatments and 2 controls, with 6 replicates each. The plants were inoculated with 3,780 eggs and J2s of the respective nematode. Throughout 150 days, the following variables were evaluated monthly: plant height, stem diameter, number of leaf pairs, and chlorophyll contents. At the end of this period (DAI), the reproductive factor (RF), egg mass and gall index were analyzed. About FR, the results were lower (<1) when using the cultivar IPR-100 when compared to the Mundo Novo genotype, denoting adequate genetic control. On the other hand, in the treatments with the susceptible genotype, high FRs were verified, ranging from 2.64 to 5.68 in the control. It was concluded that the bacterial mixtures were efficient in the control, and B. methylotrophicus contributed to higher plant height in the IPR 100 genotype.